National and Corporate Cultural Fit in Mergers/Acquisitions: An Exploratory Study - Weber, Yaakov; Shenkar, Oded; Raveh, Adi (Management Science, 1996)
While cultural fit has been acknowledged to be a potentially important factor in mergers and acquisitions, the concept has been ill-defined, with no distinction drawn between the national and corporate levels of culture. By examining both international and domestic mergers, the present study assesses the relative role of national and corporate cultural fit in predicting effective integration between merger partners. The innovative, nonparametric co-plot method is introduced, and its main advantage—the simultaneous consideration of both variables and observations—is utilized to explore cultural fit in the two groups of mergers. The findings confirm that national and corporate culture are separate constructs with variable attitudinal and behavioral correlates.